A comparison of the nutritive value of perennial ryegrass, perennial ryegrass and white clover and multispecies‐based farmlet systems - Shona Baker; Mary B. Lynch; Fionnuala Godwin; Tommy M. Boland; Alexander C. O. Evans; Paul N. C. Murphy; Alan K. Kelly; Helen Sheridan (Grassland Research, 2023)
Abstract Background Limited information is available regarding the nutritive value and structural characteristics of multispecies swards when rotationally grazed. Methods Three farmlet types were investigated in terms of their nutritive value: Lolium perenne (LP); L. perenne+Trifolium repens (LP+TR); and a multispecies sward containing grasses, legumes and herbs (MSS). Farmlets were stocked with beef steers (2.5 livestock units ha−1), grazed on a 1 ha scale to 6 cm (MSS) and 4 cm (LP and LP+TR) residuals. Results A greater ash concentration was found in MSS than LP (84 vs. 75 g kg−1 DM). Both LP+TR and MSS had higher crude protein and lower neutral detergent fibre concentrations than LP. The relative ranking of water soluble carbohydrate and dry matter (DM) concentration was LP > LP+TR > MSS. Despite the leaf component of the LP farmlet contributing more to herbage DM, the organic matter digestibilities of the swards were similar. Conclusions The MSS and LP+TR farmlets achieved similar forage quality under intensive grazing to LP. However, it is worth noting that MSS had a higher concentration of acid detergent lignin, which can negatively impact digestibility. Further investigation is needed to determine optimal grazing management practices that can minimise the effects of higher lignin concentration on digestibility in multispecies swards.